Paramagnetism of cobalt-doped ZnO nanoparticles obtained by microwave solvothermal synthesis - Wojnarowicz, Jacek; Kusnieruk, Sylwia; Chudoba, Tadeusz; Gierlotka, Stanislaw; Lojkowski, Witold; Knoff, Wojciech; Lukasiewicz, Malgorzata I.; Witkowski, Bartlomiej S.; Wolska, Anna; Klepka, Marcin T.; Story, Tomasz; Godlewski, Marek (Beilstein Journal of Nanotechnology, 2015)
Zinc oxide nanopowders doped with 1–15 mol % cobalt were produced by the microwave solvothermal synthesis (MSS) technique. The obtained nanoparticles were annealed at 800 °C in nitrogen (99.999%) and in synthetic air. The material nanostructure was investigated by means of the following techniques: X-ray diffraction (XRD), helium pycnometry density, specific surface area (SSA), inductively coupled plasma optical emission spectrometry (ICP-OES), extended X-ray absorption fine structure (EXAFS) spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and with magnetometry using superconducting quantum interference device (SQUID). Irrespective of the Co content, nanoparticles in their initial state present a similar morphology. They are composed of loosely agglomerated spherical particles with wurtzite-type crystal structure with crystallites of a mean size of 30 nm. Annealing to temperatures of up to 800 °C induced the growth of crystallites up to a maximum of 2 μm in diameter. For samples annealed in high purity nitrogen, the precipitation of metallic α-Co was detected for a Co content of 5 mol % or more. For samples annealed in synthetic air, no change of phase structure was detected, except for precipitation of Co3O4 for a Co content of 15 mol %. The results of the magentometry investigation indicated that all as-synthesized samples displayed paramagnetic properties with a contribution of anti-ferromagnetic coupling of Co–Co pairs. After annealing in synthetic air, the samples remained paramagnetic and samples annealed under nitrogen flow showed a magnetic response under the influences of a magnetic field, likely related to the precipitation of metallic Co in nanoparticles.
Keywords: cobalt-doped zinc oxide; ferromagnetism; magnetic properties; microwave solvothermal synthesis (MSS); paramagnetism